Effects of fish oil-containing lipid emulsions on retinopathy of prematurity in very low birth weight infants - Chiung-Fang Tu; Cheng-Han Lee; Hsiao-Neng Chen; Lon-Yen Tsao; Jia-Yuh Chen; Chien-Chou Hsiao (Elsevier, 2020)
Background: The aim of the study was to assess the impact of different types of parenteral emulsions on retinopathy of prematurity (ROP) in very low birth weight (VLBW, birth body weight < 1500 g) infants by comparing fish oil-containing and soy-based parenteral emulsions. Methods: Data of preterm infants with body weights below 1500 gm at birth and receiving total parenteral nutrition (TPN) for a minimum of 7 days during the period between January 2009 and November 2017 were analyzed in this retrospective study. We compared clinical outcomes in two epochs using different lipid emulsions: epoch 1 (soybean-based lipid emulsions, January 2009-February 2014) versus epoch 2 (fish oil-containing lipid emulsions, January 2015-November 2017). The primary outcomes measured were the incidence of ROP and the number of ROP cases requiring bevacizumab therapy. Results: A total of 396 infants were enrolled in this study (203 in epoch 1 and 193 in epoch 2). A lower incidence of any stage ROP (24.1 vs. 11.4%, p < 0.001) and lower requirement of bevacizumab therapy (12.8 vs. 5.2%, p = 0.001) were observed in epoch 2. Gestational age, glutamic-pyruvic transaminase, total bilirubin, and alkaline phosphatase levels, and type of lipid emulsion in TPN were associated with higher ROP incidence. Multivariate logistic regression analysis revealed that parenteral nutrition in the form of lipid emulsions containing fish oil was associated with a lower risk of development of ROP [Odds Ratio: 0.178, 95% confidence interval (CI): 0.095-0.330, p < 0.001]. Conclusions: Compared with soybean-based lipid solutions, the use of fish oil-containing lipid solutions may be associated with a lower incidence of ROP and decreased need for bevacizumab treatment in preterm infants. Key Words: fish oil, docosahexaenoic acids, n-3 polyunsaturated fatty acid, premature infants, retinopathy of prematurity